(untitled) (Bangladesh Pharmaceutical Journal, 2021)
A total of forty-five pharmaceutical tablets containing 500 mg azithromycin from 9 (nine) different companies were collected from local pharmacies and evaluated the quality of the antibiotics with standard azithromycin by physical, chromatographic (HPLC), Fourier Transform Infrared (FT-IR), and 1H & 13C Nuclear Magnetic Resonance (NMR) spectroscopic studies. Weight variation of all tested tablets were within 0.1-1.8% which is in the allowed variation of 5%. Two prominent absorption bands were observed at 1723 and 1187 cm−1 in the FT-IR spectrum of all samples and standard for the presence of >C=O and -C-O groups, respectively due to the macrocyclic lactone ring. HPLC coupled with PDA detector (at 210 and 215 nm) gave reproducible results at retention time of 10.5 min for standard and samples. The 1H and 13C NMR spectral data of the standard azithromycin and test samples were found to be identical which led to the conclusion that 1H- and 13C-NMR experiments are feasible tools for qualitative determination of azithromycin in tablets. All the described methods determined the quality of analyzed tablets well. Bangladesh Pharmaceutical Journal 24(1): 37-44, 2021